Evaluation of the effect of black soldier fly (Hermetia illucens L.) larvae meal in the diet of red drum (Sciaenops ocellatus) juveniles on production performance and feed palatability - Paredes, Juan F.; Riche, Marty; Bradshaw, David; Mejri, Sahar; Chin, Li Sun; Perez, Jasmine; Popa, Radu; Romano, Nicholas; Wills, Paul S. (Frontiers in Aquaculture, 2025)
Black soldier fly (Hermetia illucens) larvae are insects capable of valorizing various waste streams into protein that has the potential to replace fish meal (FM) in fish diets. To evaluate the feasibility of replacing FM with black soldier fly meal (BSFM) in the diet of red drum (Sciaenops ocellatus) juveniles, a two-part study was conducted that included a palatability trial followed by an 8-week feeding trial with isonitrogenous and isoenergetic formulations. Red drum is a marine and brackish-water fish species found in the Western Atlantic, ranging from Massachusetts, southern Florida, and the Gulf to northern Mexico. The palatability trial was conducted with BSFM replacing FM in diets at 0% (Control), 25% (BSFM25), 50% (BSFM50), and 100% (BSFM100) levels. The palatability assessment showed that the red drum feeding response was statistically similar between the Control and BSFM25 diets. The feeding trial included the diets above plus BSFM replacing FM at 75% (BSFM75), and the effects on growth, feeding efficiency, whole-body biochemical composition, intestinal/liver histomorphology, and intestinal microbiome were assessed. Better growth and feeding efficiency (P<0.05) were observed in fish fed the BSFM25 diet compared to those fed the BSFM50, BSFM75, and BSFM100 diets. Whole-body saturated fatty acids increased with higher levels of BSFM in the diet, while the levels of arachidonic acid (ARA), eicosapentanoic acid (EPA), and docosahexaenoic acid (DHA) remained statistically similar in BSFM25 and BSFM50 compared to the Control. Liver histomorphology revealed increased hepatic vacuolization with increasing levels of BSFM. Intestinal microbiota presented high alpha diversity abundance among the treatments, but the fish fed the BSFM diets tended to have genera associated with chitinase and lipase activity. Overall, dietary FM replacement with BSFM is an adequate alternative protein source with replacement up to 50%, but levels over 75% caused a reduction in growth and hepatic lipid accumulation.